Atributos químicos e físicos de um Latossolo sob plantio direto em zonas de manejo com diferentes produtividades - Kramer, Luiz Fernando Machado (2012)
Given the specificities of no-till (NT), crops under this system have shown specific characteristics, with different yield potentials. With the instruments of precision agriculture (PA), it is possible to map crops` productivities and other informations, as well as to establish site-specific interactions between soil attributes and yield potential what may be used to establish efficient strategies for crop management. This work aimed to study wheat grain yield and soil attributes under NT and in management zones with distinct yields, identified in a farm managed with PA techniques at South-Central Region of Paraná. The study was performed in a Farm land at Reserva do Iguaçu, evaluating two management zones with contrasting crop yields: Z1 and Z2. Regular sampling grids of 50 x 50 m (1/4 hectare) were established, with a total of 16 sampling units. For each unit, three sampling points were use to evaluate wheat grain yield and collect soil samples for the characterization of soil chemical and physical attributes. Average wheat yield at Z1 was superior (22%) to that found for Z2. Concurred for this result the fact that soil chemical fertility was lower at Z2, which also had more limiting conditions in terms of soil physics. Higher soil acidity and content of exchangeable aluminum combined to lower levels of organic carbon and basic cations were observed in Z2, especially at subsuperficial layer (0,10-0,20 m), highlighting the importance of stratified sampling of the soils under NT. Moreover, Z2 also had higher mechanical resistance to penetration (RP) (0,00-0,10 m) and bulk density (Db) (0,00-0,10 and 0,10-0,20 m), while Z1 showed higher total soil porosity (PT), due to higher macroporosity (Mac) percentage, responsible for water infiltration and soil aeration In agreement with these pore distributions, Z1 also presented higher soil basic infiltration velocity (VIB) of water. The maps of soil chemical and physical attributes showed concurrent information with the results of wheat yield mapping.